Integrating Indigenous lifestyle and NZEB (Net-Zero Energy Buildings) target while retrofitting historical heritage. A case study in the southwest of Western Australia - Strazzeri, Vittoria; Tiwari, Reena (Springer, 2023)
Net-zero energy buildings (NZEBs) are defined as highly performing buildings with minimal energy demand, which is often balanced by on-site renewable energy production. NZEBs are integrated within many national energy policies worldwide as an effective contribution toward the decarbonisation of the construction sector. The Council of Australian Government endorses the concept in the Trajectory for low energy buildings (2019) which sets a framework for improving the energy performance of new and existing buildings. Energy retrofitting against the zero-energy target offers energy-saving potential in terms of operational and embodied energy. Besides, heritage buildings retrofitting contributes to heritage management. However, the current approach to heritage buildings retrofitting aims almost exclusively to protect the physical structure and presents specific technical challenges concerning technical intervention on the building fabric and preserving the cultural heritage values. The study presents a case study of energy retrofitting of a State Heritage registered, in the south-west of WA, Carrolup Mission, which has significant cultural value for Aboriginal people. We targeted a single building assessed to be highly prioritised for the local community. We tailored the retrofitting strategy by integrating architectural design and architectural technology. We assessed the effectiveness of the retrofitting strategies against the net-zero energy target, and their impact on the buildings and the landscape. The analysis is based on building energy performance simulation (BEPS), and employs primary energy indicators to assess the building’s energy performance. The outcome is a methodological path and best practice for energy retrofitting heritage buildings against net-zero energy targets in the south-west of WA. This study highlights the relevance of including architectural consideration in energy retrofitting heritage building against energy neutrality, with a specific focus on space quality and lifestyle. We found that integrating Indigenous lifestyle and culture within the retrofitting strategy became considerably advantageous in enhancing the building space quality and provide environmental-specific sets of retrofitting strategies aiming to optimise the use of resources and the building system's efficiency. This study critically reviews the current Australian national policies concerning building energy efficiency, NZEBs and heritage retrofitting.